1981
DOI: 10.1007/bf00347590
|View full text |Cite
|
Sign up to set email alerts
|

Specialization and noncompetitive resource partitioning among sponge-eating dorid nudibranchs

Abstract: Habitat and food resource partitioning ecologically isolate six species of Pacific Northwest dorid nudibranchs. Food resources along a gradient of sponge skeletal structure are partitioned between two exploitive guilds. The guilds are characterized by mutually exclusive predatory and digestive adaptations which allow efficient processing of sponges with poorly- or well-organized skeletons. Habitats along a depth gradient are partitioned within guilds. For a dorid species, feeding rates, extraction efficiencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 65 publications
(65 reference statements)
2
16
0
Order By: Relevance
“…Competitive interactions are not necessarily implied by overlapping resource utilization (e.g. Colwell & Futuyama, 1971;Schoener, 1974;Sale, 1977;Bloom, 1981). Thus, for example, if sympatric species sharing common food items are kept below the carrying capacity of their food resources by some factor(s), such as predation or environmental variability (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Competitive interactions are not necessarily implied by overlapping resource utilization (e.g. Colwell & Futuyama, 1971;Schoener, 1974;Sale, 1977;Bloom, 1981). Thus, for example, if sympatric species sharing common food items are kept below the carrying capacity of their food resources by some factor(s), such as predation or environmental variability (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In a particularly detailed study of resource partitioning among six Pacific Northwest nudibranch species, morphological matches of sponge skeletal construction with nudibranch radula structure, and presence or absence of a caecum, played a key role in prey choice (Bloom 1976). Bloom (1981) demonstrated that competitive interactions among the nudibranchs for prey resources were not required to generate the pattern of partitioning observed, as nudibranch growth and reproduction were twice as great on their appropriate sponge species.…”
Section: Predation On Temperate and Antarctic Sponges By Invertebratesmentioning
confidence: 96%
“…Structural and chemical defenses can co-occur (Puglisi et al 2000(Puglisi et al , 2002, and trade-offs have been identified in the role that sclerites play in structure and defense (West 1998). Bloom (1981) related skeletal features of 4 species of sponge to defense against predation by sponge-eating dorid nudibranchs. While his focus was on how nudibranchs partitioned the sponge resource, he identified morphological strategies that were effective against some (but not all) predators under specific ecological conditions.…”
Section: Do Generalized Defenses Exist In Sponges?mentioning
confidence: 99%
“…Much less is known about predator-sponge dynamics in higher latitude marine habitats, despite evidence that sponges experience high rates of predation in these regions (e.g. Dayton et al 1974, Bloom 1975, 1981, Guida 1976, Thompson & Brown 1984. There are examples of chemical and structural anti-predator defenses in polar and temperate sponges (McClintock 1987, Burns & Ilan 2003, Furrow et al 2003, and contrary to expectations there appears to be no diminution of defenses with increasing latitude (Amsler et al 2000).…”
Section: Introductionmentioning
confidence: 99%